2015
DOI: 10.1007/s00455-014-9592-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prophylactic Percutaneous Endoscopic Gastrostomy (PEG) Tube Placement on Swallowing and Swallow-Related Outcomes in Patients Undergoing Radiotherapy for Head and Neck Cancer: A Systematic Review

Abstract: Patients undergoing radiotherapy for head and neck cancer (HNC) often experience malnutrition and dehydration during treatment. As a result, some centres place PEG tubes prophylactically (pPEG) to prevent these negative consequences. However, recent research has suggested that pPEG use may negatively affect swallowing physiology, function and/or quality of life, especially in the long term. The purpose of this study was to systematically review the literature on pPEG use in HNC patients undergoing radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 118 publications
(383 reference statements)
4
51
0
Order By: Relevance
“…On the basis of our quality evaluations, all included studies exhibited a risk of bias because of ineffective sampling methods, insufficient methodological rigor, and inadequate reporting. In particular, these studies involved a high risk of selection bias because of a lack of randomized sampling [32]. …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our quality evaluations, all included studies exhibited a risk of bias because of ineffective sampling methods, insufficient methodological rigor, and inadequate reporting. In particular, these studies involved a high risk of selection bias because of a lack of randomized sampling [32]. …”
Section: Discussionmentioning
confidence: 99%
“…There are concerns in the literature that gastrostomy insertion can lead to dysphagia and tube dependency (Chen et al, 2010;Corry et al, 2008;Langmore et al, 2012;Mekhail et al, 2001), although other studies have shown no detrimental impact on swallowing function (Crombie et al, 2015;Silander et al, 2010) and the body of literature remains inconclusive from a recent systematic review (Shaw et al, 2015). Whilst the data from this current study suggests there may have been more tendency for the intervention group to use the tube for supplementary feeding for longer, with an increased use at four months post-treatment, there were no other statistical differences at any other time point.…”
Section: Gastrostomy Outcomes At 12 Monthsmentioning
confidence: 97%
“…Some studies have reported nil impact on swallowing function (Crombie et al, 2015;Silander et al, 2010), and the most recent systematic review on this topic remains inconclusive (Shaw et al, 2015). As there is no agreed definition of the term gastrostomy dependency, its use can therefore be misunderstood (Talwar & Findlay, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations